Analysis of Production Process Improvement on Automatic Bolt Forming Machine Using Value Stream Mapping and FMEA Approach - Nando, Fiky Two; Ivander, Davin Danny; Sharren, Desti Sagita; Yudhistira, Christoforus; Remadaniel, Hilbram; As Shidiq, Mashudan; Sari, A.Anditha (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to analyze the production efficiency of an automatic bolt forming machine at PT XYZ using the Value Stream Mapping (VSM) and Failure Mode and Effect Analysis (FMEA) approaches. The Lean Manufacturing concept was applied to identify non-value-added activities and potential failures affecting production quality. Data were collected through direct observation, cycle time measurement, and interviews with operators and supervisors over a three-month period. The VSM results indicate that the total process time of 20,304 seconds consists of 75.64% value-added activities, 11.97% non-value-added activities, and 12.40% necessary but non-value-added activities. These findings show that efficiency improvements are still possible by minimizing non-value-adding processes. The FMEA analysis revealed the highest Risk Priority Number (RPN) of 147, occurring in the forming stage with failures such as improper heading, inaccurate trimming, and die damage. The study concludes that combining VSM and FMEA provides an effective framework for assessing process performance and determining improvement priorities to enhance efficiency and reduce product defects